Exploring Older Adults' Experiences and Coping Strategies for Loneliness: A Case Study - Jiyan Shaqilla; Irma Darmawati (STIKep PPNI Jawa Barat, 2026)
Background: Older adults are a vulnerable to physical, psychological, and social changes associated with aging, including loneliness. As loneliness can affect their psychological well-being and quality of life, understanding the coping strategies they use is essential. Objective: This study aims to explore the experiences and coping strategies of an older adult residing in a nursing home in dealing with loneliness in old age. Methods: This qualitative descriptive case study included one purposively selected older adult living in a nursing home. Data were collected using a semi-structured and non-participant observation through face-to-face interview, transcribed verbatim, and analyzed using thematic analysis by generating codes, grouping them into categories, and developing themes. This study was conducted as part of nursing care while adhering to ethical principles. Results: The findings identified three themes: feelings of loneliness and helplessness, emotional coping strategies, and social support from the shelter community. Intervies were conducted in Indonesian and Sundanese and subsequently translated into English for this manuscript. Conclusion: Participants’ experiences of loneliness were influenced by limited family interaction, nursing home living conditions, and age-realted physical and social decline. Participants used emotional regulation, self-acceptence, spiritual coping, and solitary behavior to cope with loneliness. Social support from fellow residents, staff, students, and the community helped reduce participants’ loneliness by providing emotional support and social interaction. These findings highlight routine psychosocial assessment and psychosocial interventions to reduce loneliness among older adults